2010
DOI: 10.1017/s0950268810000518
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence of a role for host genetics in susceptibility to influenza A/H5N1?

Abstract: SUMMARYThe apparent family clustering of avian influenza A/H5N1 has led several groups to postulate the existence of a host genetic influence on susceptibility to A/H5N1, yet the role of host factors on the risk of A/H5N1 disease has received remarkably little attention compared to the efforts focused on viral factors. We examined the epidemiological patterns of human A/H5N1 cases, their possible explanations, and the plausibility of a host genetic effect on susceptibility to A/H5N1 infection. The preponderanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 73 publications
4
44
0
Order By: Relevance
“…This finding is in agreement with recent studies showing that exacerbated inflammatory responses often characterize mouse strains highly susceptible to influenza infection (6,7,58). Studies on human subjects have also suggested that susceptibility to influenza is shared by close relatives and is thus a heritable property (2,29). In our studies, although we have not determined the mechanisms that underlie the rapid weight loss induced by A/California/04/09 infection, we have found that mice of the most susceptible strain, A/J, become highly resistant to virus-induced weight loss and mortality if they are preexposed to a nonpathogenic seasonal strain of H1N1 virus, suggesting that immunological memory overrides the natural susceptibility of this mouse strain to the pandemic virus.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with recent studies showing that exacerbated inflammatory responses often characterize mouse strains highly susceptible to influenza infection (6,7,58). Studies on human subjects have also suggested that susceptibility to influenza is shared by close relatives and is thus a heritable property (2,29). In our studies, although we have not determined the mechanisms that underlie the rapid weight loss induced by A/California/04/09 infection, we have found that mice of the most susceptible strain, A/J, become highly resistant to virus-induced weight loss and mortality if they are preexposed to a nonpathogenic seasonal strain of H1N1 virus, suggesting that immunological memory overrides the natural susceptibility of this mouse strain to the pandemic virus.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, influenza virus infections with inbred mouse strains have demonstrated the importance of genetic factors to variation of susceptibility to influenza (39,40). Studies with family clusters of avian influenza virus H5N1 and case studies of H1N1pdm09 patients also imply that genetic factors affect susceptibility to pandemic influenza (41)(42)(43)(44)(45). Considering the distinct genetic and epigenetic background of each donor and difference between human and mouse studies, investigating the effect of genetic or epigenetic factors on influenza susceptibility in wellcontrolled human AECs, the cells most relevant to influenza, may provide unique advantage because the response in the same type of cells will not be affected by prior influenza history, vaccination, or other environmental exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the possibility of genetic susceptibility as a risk factor for infection [41][42][43].…”
Section: Discussionmentioning
confidence: 99%